BASIC AND CLINICAL STUDIES ON FLEROXACIN IN ORAL SURGERY - MORISHIMA, TAKASHI; TOMITA, FUMISADA; SAKAMOTO, HARUO; OTA, YOSHIHIDE; SASAKI, JIRO; MORIHANA, TAKEFUMI; KANEKO, AKIHIRO (CHEMOTHERAPY, 1990)
We performed experimental and clinical studies on fleroxacin, a new synthetic antimicrobial agent for oral use, in the field of oral surgery. 1. Fleroxacin, at 200mg, was administered to 135 patients, and the concentrations in blood of fleroxacin revealed 0.45-4.43μg/ml at 141-370 min, after administration in 55 subjects. 2. A clinical study was conducted in 53 patients with odontogenic infections. The efficacy rate, judged by comparative score evaluation, was 81.6%, while that by doctors was 73.5%. Causative bacteria were isolated from 17 patients. In five cases, side-effects (insomnia, dizziness, headache) occurred. Abnormal changes in laboratory findings were noted in two cases (mild increase in eosinophils and slight elevation of BUN, s-Cr).